Slope stability analysis of two working stations Sainj and Bhatwari along the Bhagirathi valley by finite difference method - Rahul; Singh S.; Rai R.; Shrivastva B.K. (My University, 2025)
The stability analyses of hilly slopes are complex in nature. The failures of slope are devastating for men and materials. The slope stability problem in Uttarkhand region is ftequent due to steep slopes and favourable joint directions and sets. The present paper analyses the slope stability problem at Bhagirathi valley, Uttarakhand region by finite difference method. Laboratory experiments were conducted to determine the various physico-mechanical properties of rock mass. These properties have been used as input parameters to calculate the factor of safety of slopes for two working stations, Sainj and Bhatwari, along the Bhagirathi valley. The joints play very important role in the slope stability of rock mass and it reduces factor of safety significantly. It was observed that the slope of Sainj and Bhatwari is not stable in present scenario. Therefore, two methods (application of rock bolts and flattering of slope) have been proposed to stabilize the slope. It is observed the factor of safety significantly increased by reducing the slope angle or by using rock bolts. The optimum slope angles for Sainj and Bhatwari area are 51° and 59° respectively (FOS>1.5). Factor of safety of slope in Sainj area increased to 1.57 and in Bhatwari area increased up to 1.49 by application of rock bolts.